Educação Etnomatemática: ensino e formação de alfabetizadores no Projeto Alfa-Cidadã/ProneraEthno-mathematics education: teaching and training of literacy teachers in Alfa-Cidadã/Pronera project - Barros, Osvaldo dos Santos; Xavier, Antônio Roberto; Fialho, Lia Machado Fiuza (Educação Matemática Pesquisa: Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2018)
Objetiva-se compreender a possibilidade de fomentar o ensino da etnomatemática na interface com a cultura local de assentados rurais na formação de alfabetizadores do Projeto de Alfabetização Solidária na Transamazônica, parte do Programa Nacional de Educação na Reforma Agrária. Para a coleta de dados, utilizou-se a técnica de rodas de conversa para compreensão do contexto social dos alfabetizadores em formação e seleção do tema gerador: Agricultura Familiar. Os procedimentos teórico-metodológicos adotados baseiam-se em estudos que acompanham as fases da Lua. A formação etnomatemática constatou que as práticas matemáticas dos agricultores podem ser utilizadas como suporte significativo no Ensino da Matemática e que ações educativas contextualizadas dão suporte à leitura e à interpretação dos processos de objetivação do tempo. The objective is to understand the possibility of fomenting the teaching of Ethnomathematics in the interface with the local culture of rural settlers in the formation of literacy teachers of the Solidarity Literacy Project in the Transamazônica, part of the National Program of Education in Agrarian Reform. For the collection of data, we used the talk wheels technique to understand the social context of literacy teachers in training and selection of the generating theme: Family Agriculture. The theoretical-methodological procedures adopted are based on studies by Vergani (2007) that accompany the phases of the Moon with their respective meanings: “New Moon”, the awareness that the different peoples of the world have always dedicated themselves to mathematical activities (functional, symbolic, ritualistic or aesthetic); “Crescent Room”, the awareness that the mathematical activities of the different socio-cultural traditions are not reduced to mere numerical, geometric or operative practices; “Full Moon”, the awareness that Ethnomathematics has a mission in today’s world that transcends the inter-cognition of socio-cultural alterities and “Waning Room”, the consciousness of future time, in which Ethnomathematics will become just a simple historical designation linked to a certain period of human travel. The Ethnomathematics formation verified that the mathematical practices of the farmers can be used as a significant support in the Teaching of Mathematics and that contextualized educational actions support the reading and the interpretation of the processes of objectivation of the time.